MODERN MONETARY THEORY DAN EKONOMI ISLAM: MENGINTEGRASIKAN PENDEKATAN KEBIJAKAN FISKAL UNTUK PENGELOLAAN KETENAGAKERJAAN DAN INFLASI - Pamungkas, Ganda Yulida Trisakti (Investama : Jurnal Ekonomi dan Bisnis, 2026)
This study explores the integration of Modern Monetary Theory (MMT) with Islamic economic principles in addressing macroeconomic challenges such as inflation and unemployment. The research employs a descriptive-analytical qualitative approach using a comprehensive literature review methodology, analyzing data from academic journals, central bank reports, and research institutions covering the period 2012–2022. The study synthesizes MMT concepts of monetary sovereignty, money creation mechanisms, and job guarantee programs with Islamic economic principles that emphasize the state’s responsibility for social welfare and economic justice. Through a systematic examination of the similarities and differences between MMT and Islamic economics, this study demonstrates that both frameworks recognize the active role of government in regulating the economy for social purposes, prioritizing human well-being over abstract financial targets. Analysis of practical implementation during the COVID-19 pandemic, particularly Indonesia’s fiscal response and the U.S. Wage Protection Program, reveals that sovereign nations can effectively utilize fiscal capacity to maintain economic stability without triggering uncontrolled inflation. The study concludes that integrating MMT principles with Islamic economic values creates a pragmatic and ethical policy framework, enabling governments to optimize fiscal and monetary capacity for public welfare while upholding social justice and moral considerations. The novelty of this research lies in its comprehensive framework that bridges heterodox macroeconomics with Islamic economic ethics, offering a contextually relevant model for economic policymaking in Muslim-majority countries.